Tempos anormais e novas fantasias. Novas tendências em direitos humanos, justiça e educação - Carlos Vilar Estêvão (Universidade do Minho, 2015)
After characterizing the current times as abnormal times, with the creation, by the ideology of the market, of new fantasies that promise heaven on earth in terms of well-being, personal fulfillment and justice, the author makes an incursion in the land of human rights, justice, education and school, in order to unveil new interpretations, new myths, new abnormalities that are emerging within it, congruent with the market, understood as metonymy of global capitalism. In this view, rights are seen from a "multiuse" perspective, which makes them "malleable" at will and at the demands of the dominant rationality of the economy; likewise, justice tends to be construed from an individualistic and efficiency perspective, that is, as a factor that effectively contributes to the balance of trade and for maintaining the evenness of the social balance. Finally, education should constitute a sub-sector of the economy, with a functionalist format at the service of social and economic needs that come from the mercantile world.